WFS1 functions in ER export of vesicular cargo proteins in pancreatic β-cells - Linlin Wang; Hongyang Liu; Xiaofei Zhang; Eli Song; You Wang; Tao Xu; Zonghong Li (Nature Communications, 2021)
The role of cargo receptors in proinsulin export from the ER is unclear. Here, the authors identify the WFS1 protein, which is mutated in Wolfram syndrome and associated with diabetes, as an ER to Golgi cargo receptor required for normal insulin processing and secretion.